Introducing Canadian High Interest/Low Vocabulary English-Language Books into Chinese School Curriculum: The Case of Orca’s Hi-Lo Fiction - Li, Weizhang (2012)
The newly launched official edition of China’s National English Curriculum Standards (NECS) has clear requirements for the teaching of reading skills at different grades. However, acquiring such skills in a conventional English reading class is quite challenging for some students. Such difficulties parallel to some extent reading difficulties of native speakers of English in North America, which are effectively addressed by the well-established practice of using high interest/low vocabulary (Hi-Lo) reading materials. This report describes an attempt to introduce British Columbia-based Orca Book Publishers’ Hi-Lo reading series into English reading classes in Chinese secondary schools. The report argues that, to meet the demand of teaching English reading skills in the context of NECS, Orca’s English Language Teaching (ELT) Reading Package is particularly well designed to prepare Chinese secondary school students to be confident, active, critical, and fluent readers in the post-secondary academic context.